Absorbable ligation loops for flexible endoscopy: a necessary tool for natural orifice transluminal endoscopic surgery - Schoenberg, Markus B.; Ströbel, Philipp; Renteln, Daniel Alexander Patrick von; Eickhoff, Axel; Kähler, Georg (Gastrointestinal endoscopy, 2011)
Background - One of the main challenges of natural orifice transluminal endoscopic surgery (NOTES) remains the development of safe and reliable tools. In this study, we introduce the first absorbable ligatures specifically designed for NOTES. - Objective - To determine the feasibility of a new absorbable ligation loop (NOTES loop) and to compare this new type of suture with the nonabsorbable loop (Endoloop) most commonly used until now. - Design - Prospective, comparative animal trial/survival animal study (observation period 21 days) with subsequent histopathological assessment (blinded observer design). - Setting - Veterinarian center. - Subjects - This study used 12 female domestic piglets. - Intervention - Every pig underwent two transgastric uterine horn ligations, one with an absorbable loop and one with a nonabsorbable loop. Additional uterine horn resections on both sides were done on 6 pigs. - Main Outcome Measurements - Intervention success, loop reliability, foreign-body reaction, extent of inflammatory response (μm). - Results - Transgastric flexible intra-abdominal ligation of the uterine horns was performed safely with both loops in all cases. During a 3-week observation period, 11 of 11 NOTES loops and 10 of 11 Endoloops were reliable. Microscopically, foreign-body reaction was minimal around both sutures (P = .303). The overall inflammatory response was larger around the Endoloops (P = .046). Uterine horn resection had an influence on the extent of inflammation. - Limitations - Animal study. - Conclusion - Ligation was feasible with both loops. The absorbable loops were reliable during a 3-week observation period and can be recommended for use during NOTES appendectomies.
Gesehen am 07.04.2022